Cities with 'slums' : from informal settlement eradication to a right to the city in Africa - Huchzermeyer, Marie (Claremont, South Africa : UCT Press, 2011)
"The UN's Millennium Development Target to improve the lives of 100 million 'slum' dwellers has been inappropriately communicated as a target to free cities of slums. ... [The book] traces the proliferation of this misunderstanding across several African countries, and explains how current urban policy ... encourages this interpretation. The cases it presents cover a range of conflicts between poor urban residents and the local and national authorities that seek to curtail their 'right to the city'."--Back cover.
Includes bibliographical references (p. [251]-290) and index.
Keywords: Squatter settlements -- Africa; Slums -- Government policy -- Africa; Housing policy -- South Africa; Urban poor -- Housing -- Africa